Thermoplastic acetate fiber coating film as well as preparation and application thereof

By using cellulose acetate, triethyl citrate, and polyethylene glycol to prepare thermoplastic coating films, the problems of complex preparation processes, high costs, and serious pollution associated with osmotic pump controlled-release formulation coating films have been solved, achieving the effects of green environmental protection, reduced costs, and improved controlled-release efficacy.

CN121606704APending Publication Date: 2026-03-06SHANGHAI UNIV OF ENG SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610147739.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-03
Publication Date
2026-03-06

AI Technical Summary

Technical Problem

The existing coating membrane preparation process for osmotic pump controlled-release formulations is complex, costly, polluting, and has unstable membrane quality, which affects the controlled-release effect of the formulation and patient medication adherence.

Method used

Thermoplastic coating films are prepared by using cellulose acetate, triethyl citrate, and polyethylene glycol as raw materials through thermoforming or extrusion granulation, avoiding the use of organic solvents, simplifying the process, and improving film quality and production safety.

Benefits of technology

It achieves green and environmentally friendly production, reduces costs, improves production safety, and facilitates large-scale production. Moreover, its controlled-release effect is no weaker than that of existing commercially available controlled-release tablets, and it is suitable for sustained-release or controlled-release formulations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121606704A_ABST
    Figure CN121606704A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of pharmaceutical preparations, and particularly relates to an acetate fiber thermoplastic coating film as well as preparation and application thereof. The cellulose acetate thermoplastic coating film is prepared by thermoforming cellulose acetate, triethyl citrate and polyethylene glycol which are uniformly mixed as raw materials. The preparation process is high in automation and scale degree, low in environment and equipment requirements, green and environment-friendly, capable of reducing loss and suitable for industrial production. The sustained and controlled release preparation prepared from the cellulose acetate fiber thermoplastic coating film has a good sustained and controlled release effect, and a new coating direction is provided for preparation of the sustained and controlled release preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pharmaceutical preparations, and particularly relates to a pharmaceutical polymer material, specifically a cellulose acetate thermoplastic coating film and its preparation and application. Background Technology

[0002] In recent years, with the accelerated aging of the population and the combined effects of lifestyle and environmental factors, chronic non-communicable diseases have become a major challenge threatening public health and socio-economic development. Chronic diseases are typically characterized by long course and the need for long-term or even lifelong treatment. Patients often need to take medication regularly and continuously to maintain stable blood drug concentrations in order to effectively control disease progression and reduce the risk of complications and death.

[0003] However, in actual clinical applications, conventional oral immediate-release formulations often suffer from problems such as high dosing frequency, large fluctuations in blood drug concentration, and significant peak-to-trough differences. This not only increases the risk of poor patient compliance, missed doses, and discontinuation of medication, but may also lead to unstable efficacy and exacerbated toxic side effects, thus affecting long-term treatment outcomes. To address this issue, controlled-release formulations have emerged, among which osmotic pump controlled-release technology has attracted much attention due to its unique advantages. Osmotic pump controlled-release tablets, through a special design of a semi-permeable membrane and release pores, utilize the osmotic pressure generated by gastrointestinal fluid entering the tablet core to drive a stable release of the drug at a near-zero-order rate, almost unaffected by external environmental factors such as gastrointestinal pH, food intake, or physiological state. For patients with chronic diseases, this means that the drug can maintain a stable blood drug concentration for a longer period, reducing the frequency of daily dosing, significantly improving medication compliance, and reducing the risk of side effects caused by drug concentration fluctuations, thereby improving long-term efficacy and quality of life.

[0004] The preparation of osmotic pump controlled-release formulations mainly includes several key steps such as core preparation, coating, perforation, and post-processing. The first step is core preparation, which, depending on the drug's physicochemical properties and design requirements, generally consists of a drug layer and a propellant layer. The drug layer typically involves granulating the active ingredient with excipients such as diluents, disintegrants, binders, and lubricants to achieve good tableting and release characteristics. The propellant layer primarily consists of high-osmotic-pressure substances (such as sodium chloride) and high-molecular-weight expanding agents (such as hydroxypropyl methylcellulose and polyethylene oxide), which rapidly expand upon the infiltration of water, providing a continuous and stable propellant force. Subsequently, the drug layer and propellant layer are compressed into a bilayer or multilayer drug-eluting chip using a tableting process, forming the core of the osmotic pump controlled-release system.

[0005] Secondly, there is the coating process, which involves coating the drug core with a semi-permeable membrane. The design of the semi-permeable membrane is crucial, as it determines the rate of water permeation and the integrity of the membrane. It must allow water molecules to pass through but not the drug, thereby ensuring the formation of the osmotic pressure-driven effect.

[0006] Next is the perforation process, which typically uses laser perforation technology to precisely create one or more micropores on the semi-permeable membrane. The pore size is generally controlled within tens of micrometers, allowing the drug to be stably released through the micropores after entering the drug core in body fluids.

[0007] Finally, post-processing and quality control are carried out, including testing membrane thickness, tablet hardness, and drug release pore size, and verifying the controllability and repeatability of drug release through in vitro dissolution tests. The key to the entire preparation process lies in the rationality of the drug core formulation, the optimization of the semi-permeable membrane material and thickness, and the precision of the micropore design. These three factors together determine whether the osmotic pump formulation can achieve the ideal zero-order release characteristics.

[0008] Compared with ordinary tablets, the preparation process of osmotic pump controlled-release formulations is more complex, but its advantage lies in the fact that the drug release process is almost unaffected by the gastrointestinal environment, which can significantly improve the in vivo and in vitro correlation of the formulation and ensure long-term, stable and predictable drug release. This is of great significance for long-term treatment of chronic diseases and improving patient medication adherence.

[0009] In osmotic pump controlled-release formulations, the coating membrane, typically a semi-permeable membrane, is a key structure for achieving controlled release. It selectively allows water to pass through, preventing direct drug diffusion. Water enters the tablet core, creating osmotic pressure that propels the drug through the membrane's pores at a constant release rate. The thickness, material, and pore-forming agent ratio of the coating membrane determine the release rate and stability, ensuring not only controlled-release efficacy and batch-to-batch consistency but also extending the duration of action, reducing dosing frequency and side effects, and significantly improving patient compliance. Currently, most osmotic pump controlled-release formulations use spray coating, a process that often employs flammable and explosive organic solvents, resulting in high workshop construction costs; large solvent consumption, severe environmental pollution, and high recovery costs; wasted coating droplets during coating, exacerbating pollution; and the highly experience-dependent nature of spray coating operations, with numerous influencing factors making it difficult to obtain a stable and uniform membrane layer. Furthermore, the post-coating drying process is lengthy. The complex preparation processes, demanding conditions, and unstable membrane quality of existing coating membranes lead to unsatisfactory effects and high costs for osmotic pump controlled-release formulations. Summary of the Invention

[0010] To address the numerous problems of existing coating technologies, this invention provides a preparation technology for thermoplastic coating films. This preparation technology eliminates the use of organic solvents commonly used in traditional spray coating, and the prepared coating film exhibits excellent controlled-release properties, with a controlled-release effect no weaker than that of existing commercially available controlled-release tablets.

[0011] The technical solution of this invention is a thermoplastic coating film, which is prepared by thermoforming a mixture of cellulose acetate, triethyl citrate, and polyethylene glycol as raw materials. The cellulose acetate comprises 50-70 parts by weight, the triethyl citrate 15-25 parts by weight, and the polyethylene glycol 6-10 parts by weight. The polyethylene glycol is polyethylene glycol 1500.

[0012] The thermoforming step includes: melting and casting a mixture of cellulose acetate, triethyl citrate, and polyethylene glycol into a film; or, First, the mixed cellulose acetate, triethyl citrate, and polyethylene glycol are melt-extruded and granulated to obtain masterbatch; The masterbatch is then melted and cast into a film.

[0013] The screw temperature for melt casting of the mixed cellulose acetate, triethyl citrate, and polyethylene glycol is 165℃-185℃, the die temperature is 185℃-190℃, and the screw speed is 190-200 rpm. In one embodiment, the screw temperature is set to 170℃ for zone 1-2, 175℃ for zone 3-4, 180℃ for zone 5-6, 185℃ for zone 7-8, and 185℃ for the transition zone, while the die temperature is 190℃.

[0014] The screw temperature for melt extrusion granulation of the mixed cellulose acetate, triethyl citrate, and polyethylene glycol is 131℃-178℃, the die temperature is 175℃-180℃, and the screw speed is 40-50 rpm. In one embodiment, the screw temperature is set as follows: zone 1 131℃, zone 2 153℃, zones 3-6 169℃, zone 7 173℃, zone 8 175℃-178℃, and the die temperature is 176℃-180℃.

[0015] The screw temperature for melt casting of the masterbatch is 170℃-210℃, the die temperature is 195℃-230℃, and the screw speed is 30-40 rpm. Further, the screw temperature is set to zone 1: 170℃, zone 2: 175℃-185℃, zone 3: 180℃-190℃, and the transition zone: 186℃-190℃; the die temperature is 195℃-220℃. As one embodiment, the screw temperature is set to zone 1: 170℃, zone 2: 185℃, zone 3: 190℃, and the transition zone: 190℃; the die temperature is 198℃.

[0016] The mixing steps for cellulose acetate, triethyl citrate, and polyethylene glycol include: mixing molten polyethylene glycol and triethyl citrate under heating conditions, followed by mixing with cellulose acetate. Specifically, polyethylene glycol is heated to molten state at 70°C-80°C for 60-70 minutes. The molten polyethylene glycol and triethyl citrate are mixed at 70°C-80°C until no polyethylene glycol solids precipitate. After mixing the molten polyethylene glycol and triethyl citrate under heating conditions, they are then mixed with cellulose acetate in a high-speed mixer for 45-60 minutes, and then passed through a 20-mesh sieve.

[0017] The mixed cellulose acetate, triethyl citrate, and polyethylene glycol are first dried and then thermoformed, specifically dried at 55℃-70℃ for 7-10 days. The cellulose acetate is first dried at 75℃-85℃ for 40-50 hours before being mixed with the triethyl citrate and polyethylene glycol.

[0018] This invention also provides a method for preparing a thermoplastic coating film, comprising the steps of: melting and casting a mixture of cellulose acetate, triethyl citrate, and polyethylene glycol into a film; or, First, the mixed cellulose acetate, triethyl citrate, and polyethylene glycol are melt-extruded and granulated to obtain masterbatch; The masterbatch is then melted and cast into a film.

[0019] The cellulose acetate is 50-70 parts by weight, triethyl citrate is 15-25 parts by weight, and polyethylene glycol is 6-10 parts by weight. The polyethylene glycol is polyethylene glycol 1500.

[0020] The screw temperature for melt casting of the mixed cellulose acetate, triethyl citrate, and polyethylene glycol is 165℃-185℃, the die temperature is 185℃-190℃, and the screw speed is 190-200 rpm. In one embodiment, the screw temperature is set to 170℃ for zone 1-2, 175℃ for zone 3-4, 180℃ for zone 5-6, 185℃ for zone 7-8, and 185℃ for the transition zone, while the die temperature is 190℃.

[0021] The screw temperature for melt extrusion granulation of the mixed cellulose acetate, triethyl citrate, and polyethylene glycol is 131℃-178℃, the die temperature is 175℃-180℃, and the screw speed is 40-50 rpm. In one embodiment, the screw temperature is set as follows: zone 1 131℃, zone 2 153℃, zones 3-6 169℃, zone 7 173℃, zone 8 175℃-178℃, and the die temperature is 176℃-180℃.

[0022] The screw temperature for melt casting of the masterbatch is 170℃-210℃, the die temperature is 195℃-230℃, and the screw speed is 30-40 rpm. Further, the screw temperature is set to zone 1: 170℃, zone 2: 175℃-185℃, zone 3: 180℃-190℃, and the transition zone: 186℃-190℃; the die temperature is 195℃-220℃. As one embodiment, the screw temperature is set to zone 1: 170℃, zone 2: 185℃, zone 3: 190℃, and the transition zone: 190℃; the die temperature is 198℃.

[0023] The mixing steps for cellulose acetate, triethyl citrate, and polyethylene glycol include: mixing molten polyethylene glycol and triethyl citrate under heating conditions, followed by mixing with cellulose acetate. Specifically, polyethylene glycol is heated to molten state at 70°C-80°C for 60-70 minutes. The molten polyethylene glycol and triethyl citrate are mixed at 70°C-80°C until no polyethylene glycol solids precipitate. After mixing the molten polyethylene glycol and triethyl citrate under heating conditions, they are then mixed with cellulose acetate in a high-speed mixer for 45-60 minutes, and then passed through a 20-mesh sieve.

[0024] The mixed cellulose acetate, triethyl citrate, and polyethylene glycol are first dried before being cast into a film or melt-extruded into granules, specifically dried at 55℃-70℃ for 7-10 days. The cellulose acetate is dried before being mixed with triethyl citrate and polyethylene glycol, specifically dried at 75℃-85℃ for 40-50 hours.

[0025] The thermoplastic coating film provided by the present invention can be used to prepare sustained-release or controlled-release formulations, including but not limited to tablets or capsules. The thermoplastic coating film provided by the present invention serves as a sustained-release or controlled-release membrane layer for sustained-release or controlled-release formulations.

[0026] A sustained-release or controlled-release formulation contains a thermoplastic coating film as described above. The thermoplastic coating film provided above serves as the sustained-release or controlled-release film layer of the sustained-release or controlled-release formulation, which includes, but is not limited to, tablets or capsules.

[0027] Furthermore, the thermoplastic coating film of the present invention is provided with drug release pores. Specifically, when manufacturing sustained-release or controlled-release tablets, the drug release pores are located at the center of both sides of the tablet, with a pore diameter of approximately 70 micrometers.

[0028] Compared with existing technologies, the present invention has the following advantages: (1) Green and environmentally friendly: No organic solvents are used in the entire preparation process, which avoids the air pollution and adverse environmental impact caused by the volatilization of large amounts of solvents in traditional processes, and is more in line with the requirements of green pharmaceuticals and sustainable development.

[0029] (2) Reduce raw material costs: Since the use of organic solvents is completely eliminated, not only are expensive solvent procurement costs saved, but also the hidden costs caused by solvent loss and emissions are reduced, thereby significantly reducing the overall input of raw materials for production.

[0030] (3) Reduce process steps and lower production costs: The technology of this invention does not require the setting of complex organic solvent recovery devices, nor does it need to be produced in expensive explosion-proof workshops. This not only simplifies the production process, but also reduces the investment in factory construction and equipment, further reducing the production costs of enterprises.

[0031] (4) Improve production safety: Since the use of organic solvents is completely eliminated, the safety hazards of flammable and explosive solvents are naturally eliminated, which fundamentally improves the safety of operators and equipment in the production process.

[0032] (5) Facilitates large-scale and automated production: This process has good continuity and stability, and can run smoothly on the production line for a long time, avoiding frequent shutdowns, thus making it more conducive to automated production and large-scale industrial application. Attached Figure Description

[0033] Figure 1 It is a picture of cellulose acetate powder.

[0034] Figure 2 It is a picture of a powder made by mixing cellulose acetate, triethyl citrate, and polyethylene glycol.

[0035] Figure 3 The image shows a masterbatch obtained by melt extrusion granulation of a mixture of cellulose acetate, triethyl citrate, and polyethylene glycol.

[0036] Figure 4 This is a photograph of the thermoplastic coating film prepared by the one-step method in Example 1.

[0037] Figure 5 This is a photograph of the thermoplastic coating film prepared by the two-step method in Example 4.

[0038] Figure 6 It is a metformin hydrochloride thermoplastic coated tablet prepared using the thermoplastic coating film of Example 4.

[0039] Figure 7 The thermogravimetric curves are shown for the thermoplastic coating film prepared by the one-step method in Example 1 and the thermoplastic coating film prepared by the two-step method in Example 4.

[0040] Figure 8 The release curves (n=4) are for metformin hydrochloride thermoplastic coated tablets prepared using the thermoplastic coating film of Example 1, metformin hydrochloride thermoplastic coated tablets prepared using the thermoplastic coating film of Example 4, and commercially available metformin hydrochloride sustained-release tablets. Detailed Implementation

[0041] The technical solution of the present invention will be illustrated below with specific examples, but these are not intended to limit the scope of protection of the present invention.

[0042] Example 1: Preparation of cellulose acetate thermoplastic coating film in one step Step 1: Material Preparation Weigh out 63 parts by weight of cellulose acetate, 22 parts by weight of triethyl citrate, and 9 parts by weight of polyethylene glycol 1500.

[0043] Cellulose acetate was dried in an oven at 80 °C for 48 h to remove all moisture.

[0044] Polyethylene glycol 1500 was heated in a water bath at 70 °C for 60 min until it was completely melted; then it was poured into a container containing triethyl citrate and stirred continuously at 80 °C until it was mixed evenly and no more polyethylene glycol 1500 solids precipitated out.

[0045] Step 2: Material Mixing The cellulose acetate from step one, the mixed triethyl citrate and polyethylene glycol 1500 were placed in a high-speed mixer and mixed for 60 minutes to ensure that the material could pass through a 20-mesh sieve. The resulting material was then placed in a 60°C oven and dried for 8 days. Step 3: Casting and Film Formation The material mixed in step two is extruded into a film in a twin-screw casting machine. The screw temperature is set to 170℃ in zone 1-2, 175℃ in zone 3-4, 180℃ in zone 5-6, 185℃ in zone 7-8, and 185℃ in the transition zone. The die temperature is 190℃ and the screw speed is 200 rpm.

[0046] The thickness of the cellulose acetate thermoplastic coating film can be adjusted as needed, such as to prepare 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, etc.

[0047] Example 2 The preparation method of this embodiment is the same as that of Example 1, except that: 50 parts by weight of cellulose acetate coating film, 15 parts by weight of triethyl citrate, and 6 parts by weight of polyethylene glycol 1500.

[0048] Example 3 The preparation method of this embodiment is the same as that of Example 1, except that: 70 parts by weight of cellulose acetate coating film, 25 parts by weight of triethyl citrate, and 10 parts by weight of polyethylene glycol 1500.

[0049] Example 4: Preparation of cellulose acetate thermoplastic coating film using a two-step method Step 1: Material Preparation The procedure for this step is the same as in Example 1.

[0050] Step 2: Material Mixing The procedure for this step is the same as in Example 1.

[0051] Step 3: Extrusion Granulation The material mixed in step two is extruded and granulated in a twin-screw extruder. The screw temperature is set to 131℃ in zone 1, 153℃ in zone 2, 169℃ in zones 3-6, 173℃ in zone 7, and 176℃ in zone 8. The die temperature is 178℃, and the screw speed is 40 rpm, which converts the material into granular masterbatch.

[0052] Step 4: Casting and Film Formation The masterbatch obtained in step 3 was cast into a film in a single-screw casting machine. The screw temperature was set to 170℃ in zone 1, 175℃ in zone 2, 180℃ in zone 3, and 186℃ in the transition zone. The die temperature was 220℃ and the screw speed was 40 rpm.

[0053] The thickness of the cellulose acetate thermoplastic coating film can be adjusted as needed, such as to prepare 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, etc.

[0054] from Figure 4 and Figure 5 It can be seen that there is no significant difference in appearance between the cellulose acetate thermoplastic coating films prepared by the one-step method and the two-step method.

[0055] Example 5 Step 1: Material Preparation This step is the same as in Example 4.

[0056] Step 2: Material Mixing This step is the same as in Example 4.

[0057] Step 3: Extrusion Granulation This step is the same as in Example 4.

[0058] Step 4: Casting and Film Formation This step is the same as in Example 4, except that the screw temperature is set to 170°C in zone 1, 185°C in zone 2, 190°C in zone 3, 190°C in the transition zone, and the die head temperature is 198°C.

[0059] Compared to Example 4, the cellulose acetate thermoplastic coating film prepared in this example is easier to form and more stable in forming, and its performance is better than that of the cellulose acetate thermoplastic coating film prepared in Example 4.

[0060] Example 6: Thermogravimetric Experiment Thermogravimetric analysis (TGA) measures the change in mass of a substance with temperature during heating. This allows us to understand important information such as the material's thermal stability, decomposition temperature, water content, volatile matter content, and residue content, thereby determining the chemical changes and compositional characteristics of the material when heated.

[0061] Depend on Figure 7It can be seen that the thermogravimetric curves of the cellulose acetate thermoplastic coating films prepared by the one-step and two-step methods almost completely overlap, with only a slight difference at about 250℃. This difference mainly stems from the different processing times of the two processes, resulting in a slight difference in the degree of loss of triethyl citrate during processing, thus exhibiting a subtle difference in mass change at this temperature range.

[0062] Example 7: Dissolution test The drug delivery performance of osmotic pump controlled-release tablets largely depends on their drug release behavior; therefore, in vitro release rate determination plays a crucial role in the research of this type of formulation. These formulations regulate the entry of the dissolution medium through a semi-permeable membrane. After the medium permeates into the tablet core, it forms an osmotic pressure gradient, thereby driving the sustained, controlled release of the drug through the release pores. Ideally, the osmotic pump system can maintain a relatively stable release rate over a considerable period, exhibiting near-zero-order release characteristics.

[0063] In vitro release assays can evaluate the drug release behavior of osmotic pump controlled-release tablets from an experimental perspective, serving as an important basis for determining whether their controlled-release performance meets design expectations. Furthermore, this method can be used to systematically investigate the impact of changes in formulation factors and structural parameters on drug release behavior, such as the properties of the coating material, membrane structure, and pore design, providing quantitative references for formulation optimization and process parameter selection.

[0064] The surface of a circular metformin hydrochloride core was coated with a thermoplastic coating film (80 μm) prepared in Example 1 and a thermoplastic coating film (50 μm and 80 μm) prepared in Example 4, respectively. A hole (drug release hole) was punched in the center of the cellulose acetate thermoplastic coating film on both sides of the tablet, with a pore size of about 70 micrometers, to obtain a metformin hydrochloride thermoplastic coated tablet.

[0065] The study compared the differences in in vitro release rates of tablets prepared from cellulose acetate thermoplastic coating films using two different processes, and further analyzed the effect of different coating film thicknesses on the drug release behavior of the formulation. Meanwhile, commercially available metformin hydrochloride tablets were used as a reference formulation for a comparative study.

[0066] The results are as follows Figure 8 As shown, under the condition that the coating film thickness is 80 μm, the tablets prepared with cellulose acetate thermoplastic coating films prepared by different processes exhibit highly consistent in vitro release behavior, with their release curves essentially overlapping. When the coating film thickness is reduced to 50 μm, the drug release rate of the formulation is significantly accelerated. These results indicate that the coating film thickness is an important factor affecting the drug release rate of osmotic pump controlled-release tablets, and the drug release rate can be effectively adjusted by controlling the coating film thickness.

[0067] like Figure 8As shown, the cellulose acetate thermoplastic coating film prepared by this invention has a release rate curve similar to that of commercially available metformin hydrochloride tablets. The cellulose acetate thermoplastic coating films prepared in Examples 2, 3, and 5 have similar or better properties than those prepared in Examples 1 and 4.

Claims

1. A thermoplastic coating film characterized by, The hot forming is made from mixed cellulose acetate, triethyl citrate and polyethylene glycol, wherein the cellulose acetate is 50-70 parts by mass, the triethyl citrate is 15-25 parts by mass, and the polyethylene glycol is 6-10 parts by mass.

2. A film according to claim 1, wherein The hot forming step comprises: mixed cellulose acetate, triethyl citrate and polyethylene glycol melt casting film; or, First, the mixed cellulose acetate, triethyl citrate and polyethylene glycol are melt extruded and granulated to obtain a master batch; Then, the master batch is melt casted into a film.

3. A film according to claim 1, wherein the thermoplastic coating film is characterized by The mixing step of the cellulose acetate, triethyl citrate and polyethylene glycol comprises: mixing the heated and melted polyethylene glycol with the triethyl citrate under heating conditions, and then mixing with the cellulose acetate.

4. A film according to claim 1, wherein The mixed cellulose acetate, triethyl citrate and polyethylene glycol are first dried and then hot formed.

5. A process for the preparation of a thermoplastic coating film, characterized by the steps of Comprise: Mixed cellulose acetate, triethyl citrate and polyethylene glycol melt casting film; Or, First, the mixed cellulose acetate, triethyl citrate and polyethylene glycol are melt extruded and granulated to obtain a master batch; Then, the master batch is melt casted into a film.

6. The production method according to claim 5, wherein The cellulose acetate is 50-70 parts by mass, the triethyl citrate is 15-25 parts by mass, and the polyethylene glycol is 6-10 parts by mass.

7. The preparation method according to claim 5, characterized in that, The mixing step of the cellulose acetate, triethyl citrate and polyethylene glycol comprises: mixing the heated and melted polyethylene glycol with the triethyl citrate under heating conditions, and then mixing with the cellulose acetate.

8. The preparation method according to claim 5, characterized in that, The mixed cellulose acetate, triethyl citrate and polyethylene glycol are first dried and then casted into a film or melt extruded and granulated.

9. The use of a thermoplastic coating film according to any one of claims 1-4 for preparing a sustained or controlled release preparation.

10. A sustained or controlled release formulation, characterized in that, A thermoplastic coating film according to any one of claims 1-4. A thermoplastic coating film according to any one of claims 1-4.

Citation Information

Patent Citations

  • Coating diaphragm for fast thermoplastic coating preparation and preparation method thereof

    CN108619523A

  • Preparation method of phosphoric acid-ligustrazine micro-porous osmotic pump controlled release tablet

    CN108815128A

  • Coating film for tablets and preparation method thereof

    CN118986912A

  • Timing controlled – release porous tablet of diltiazem hydrochloride and the preparation method thereof

    WO2010081286A1